A retrospective study of ectopic pregnancies in a tertiary care hospital - Murugesan, Anuradha; Prabhu, Karthiga; M., Muthulakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ectopic pregnancy is a common life threatening emergency in first trimester of pregnancy and it leads to serious maternal morbidity and also can cause mortality. The aim was to study the incidence, clinical presentation, risk factors and the management of patients with ectopic pregnancies admitted in our hospital over three year period. Methods: The present study involves a retrospective analysis of ectopic pregnancies admitted in SRM Medical college hospital for three years from 2012 to 2015. Results: The incidence of ectopic pregnancy in the present study is 1.77%. About 79% of the women were in the age group of 21-30 years. About 79% of patients in present study belonged to low socioeconomic status. In the study ectopic pregnancies were more common among multigravida (78%). 73% of patients had identifiable risk factors of which tubal surgeries were more common (31.15%). Ultrasound was diagnostic of ectopic pregnancy in 85% of patients. 97.26% were tubal ectopic pregnancies and 2.74% were ovarian ectopic pregnancies. Among tubal pregnancies majority of cases were ampullary pregnancies (62%). All patients in the study underwent surgical management. Conclusions: Ectopic pregnancy is still a major challenge in gynaecological practice. Early diagnosis and early referral is the key to successful management. It is better to over diagnose an ectopic pregnancy especially in a rural setup. Most cases present late, making tubal conservation treatment inapplicable. The impact on future fertility can be improved by focusing on primary prevention and early diagnosis before rupture so that conservation treatment can be done.